Aplikasi Teknologi Program Pengembangan Produk Unggulan Daerah (PPPUD); Produksi Ikan Hias Karang Lestari di Pulau Barrang Lompo, Makassar, Sulawesi Selatan - Akmal Abdullah; Mauli Kasmi; Karma; Ilyas (Universitas Lancang Kuning, 2020)
The potential of fishery resources in Indonesia is very abundant especially in South Sulawesi but has not been utilized to the fullest. This is because there is a lack of mastery of technological innovation handling coral ornamental fish, especially the production of marine ornamental fish. The objective of the Regional product development Program is to develop the business activities of a group of fishermen who are more self-reliant economically profitable and social, creating tranquility, comfort in community life and improving skills in a softskill and Hardskill, the number and quality of products increased to market, the product markets can be broadly open to export products, environmental health improvement, The method used is the socialization of PPPUD program. Training on how to capture and handle ornamental fish using Cleopatra nets and clove oil, operationalization and monitoring and evaluation program to ensure the sustainability and development of this PPPUD. The solutions offered in this activity is a more efficient decorative fish business management system and the results of ornamental fish products that are the standard export that will be applied to the East Marine SMES, as well as the implementation of the SME management system.